EKSPLORASI LITERASI GURU SEKOLAH DASAR DALAM PRAKTIK PENGEMBANGAN BAHAN AJAR BAHASA INDONESIA DI DESA HUMENE SATUA, GUNUNGSITOLI - Masherniwati Tanjung; Friska Ria Sitorus; Izmawal Pebriani Nasution (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Teacher literacy plays an important role in the development of instructional materials, particularly at the elementary school level where teachers are expected to design contextual and meaningful learning resources. However, studies on teacher literacy in schools with limited learning resources remain limited. This study aims to describe the literacy practices of elementary school teachers in developing Indonesian language teaching materials and to identify the supporting and inhibiting factors influencing these practices. This research employed a qualitative approach using a descriptive case study design. The participants consisted of four elementary school teachers in Humene Satua Village, Gunungsitoli, who were selected purposively. Data were collected through in-depth interviews and classroom observations and analyzed using data reduction, data display, and conclusion drawing. The findings indicate that teachers have an adequate awareness of literacy, but the implementation of reading literacy, information literacy, digital literacy, and pedagogical literacy is still not optimal. Teachers tend to rely on textbooks, use internet resources selectively, and utilize digital technology at a basic level. Supporting factors include teachers’ intrinsic motivation and principal support, while inhibiting factors include limited learning resources, minimal digital literacy training, and high administrative workload. Strengthening teacher literacy through improved access to learning resources and continuous professional development is essential to enhance the quality of instructional materials and learning in elementary schools.